The construction of a new technological innovation system in a follower country: wind energy in Portugal - Bento, N.; Fontes, M. (Technological Forecasting and Social Change, 2015)
This article analyzes the process of construction of a new innovation system based on wind energy in a “follower” context. The technological innovation systems framework is used to analyze the process of technology diffusion as well as the emergence of a new wind sector in Portugal, where this renewable energy technology showed a spectacular development in the past decade. This framework highlights the main processes or functions that occur in the diffusion of a new technology. The evidence obtained demonstrates that the fulfillment of these functions, which were mostly studied in the context of pioneer countries, is still pertinent to explain the formation of a wind energy system in this follower country. Yet the type of resources and the nature of the activities needed to adopt the technology in the latter often differ. This case provides new insights into the importance of functions that enhance the follower's capacity to assimilate the new technology (e.g. local knowledge development, experimentation), thus creating the conditions for a fast move as soon as innovations become sufficiently mature in the core.